2015
DOI: 10.1038/nrendo.2015.189
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metabolism by the innate immune system

Abstract: Low-grade tissue inflammation induced by obesity can result in insulin resistance, which in turn is a key cause of type 2 diabetes mellitus. Cells of the innate immune system produce cytokines and other factors that impair insulin signalling, which contributes to the connection between obesity and the onset of type 2 diabetes mellitus. Here, we review the innate immune cells involved in secreting inflammatory factors in the obese state. In the adipose tissue, these cells include proinflammatory adipose tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
505
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(544 citation statements)
references
References 197 publications
14
505
0
7
Order By: Relevance
“…We propose that in the context of HFD and/or obesity, intestinal barrier leakage may prevent the ability of preabsorptive nutrients to accumulate in the small intestine, leading to an inability to trigger the gut-derived peptide network to regulate postprandial glucose homeostasis (Figure 2). In parallel, a leak of nutrients into the circulation and tissues such as liver, muscle, fat, and brain might also disrupt glucose homeostasis by inducing insulin resistance and/or inflammation in target tissues, resulting in a positive feedback loop to disrupt glucose homeostasis (10,11,110,111).…”
Section: Figure 2 An Integrative and Neuronal-dependent Intestinal Imentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that in the context of HFD and/or obesity, intestinal barrier leakage may prevent the ability of preabsorptive nutrients to accumulate in the small intestine, leading to an inability to trigger the gut-derived peptide network to regulate postprandial glucose homeostasis (Figure 2). In parallel, a leak of nutrients into the circulation and tissues such as liver, muscle, fat, and brain might also disrupt glucose homeostasis by inducing insulin resistance and/or inflammation in target tissues, resulting in a positive feedback loop to disrupt glucose homeostasis (10,11,110,111).…”
Section: Figure 2 An Integrative and Neuronal-dependent Intestinal Imentioning
confidence: 99%
“…Multiple factors contribute to insulin resistance and glucose dysregulation in obesity and diabetes, but chronic low-grade inflammation of metabolic tissues, including visceral adipose tissue (VAT), liver, and brain, are important contributors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The intestinal immune system has recently emerged as a site that is altered by diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism by which obesity causes insulin resistance is unclear, inflammation has been linked to the development of local and systemic insulin resistance, especially when the inflammation occurs in white adipose tissue (WAT) (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, dysregulated or prolonged inflammation states have been associated with many diseases, including type 2 diabetes [1]. Early connections between inflammation, obesity and type 2 diabetes were made in the 1990s, in both rodent models and humans [2,3], and later substantiated by a large body of evidence (see [4][5][6][7] for recent reviews). Then, it was observed that pancreatic islet cells may also show signs of inflammation, including immune cell infiltration [8][9][10] and increased expression of cytokines and chemokines [11][12][13].…”
Section: Introductionmentioning
confidence: 99%